2022
DOI: 10.12998/wjcc.v10.i21.7565
|View full text |Cite
|
Sign up to set email alerts
|

Spinal giant cell-rich osteosarcoma-diagnostic dilemma and treatment strategy: A case report

Abstract: BACKGROUND Giant cell-rich osteosarcoma (GCRO) is a rare histological variant of osteosarcoma. Spinal GCROs are extremely rare, with challenging diagnosis and management. Herein, we present a case of spinal GCRO at T2, which was not diagnosed in initial biopsy but after T2 corpectomy. We detailed the clinical course, management strategy, and outcome after a 4-year follow-up. CASE SUMMARY A 17-year-old female patient presented with back pain followed by ascending paresth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Literature search revealed 56 cases of GCRO published between 1986 and 2022 in a total of 34 studies, with 36 cases reported from Asia (64%; Table 3). 10–12,18–50 Mean age was 26 years (range, 5–73 years) and 28 were males (50%). Localizations were reported as follows: Femur (38%; n = 21; 10 times distal, 8 times diaphyseal, 2 times proximal, 1 time unspecified), tibia (27%; n = 15; 14 times proximal, 1 time diaphyseal), mandible ( n = 5), vertebrae C6 to T6 ( n = 4), maxilla ( n = 2), proximal fibula ( n = 2), proximal ulna ( n = 2), foot ( n = 2; first metatarsal, medial cuneiform), 11th rib ( n = 1), skull base ( n = 1), and distal radius ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Literature search revealed 56 cases of GCRO published between 1986 and 2022 in a total of 34 studies, with 36 cases reported from Asia (64%; Table 3). 10–12,18–50 Mean age was 26 years (range, 5–73 years) and 28 were males (50%). Localizations were reported as follows: Femur (38%; n = 21; 10 times distal, 8 times diaphyseal, 2 times proximal, 1 time unspecified), tibia (27%; n = 15; 14 times proximal, 1 time diaphyseal), mandible ( n = 5), vertebrae C6 to T6 ( n = 4), maxilla ( n = 2), proximal fibula ( n = 2), proximal ulna ( n = 2), foot ( n = 2; first metatarsal, medial cuneiform), 11th rib ( n = 1), skull base ( n = 1), and distal radius ( n = 1).…”
Section: Resultsmentioning
confidence: 99%